2003
DOI: 10.1046/j.1365-2109.2003.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton and epibenthic fauna in shrimp ponds: factors influencing assemblage dynamics

Abstract: The assemblage composition, biomass and dynamics of zooplankton and epibenthos were examined in a commercial shrimp (penaeid prawn) pond in subtropical Australia. Physicochemical characteristics of the pond water were measured concurrently. Numbers and biomass of zooplankton in the surface tows (140 mm mesh) varied from 111.7 ind. L À1 (324 mg L À1 ) to 8.3 ind. L À1 (44.2 mg L À1 ). Immediately after the ponds were stocked with shrimp postlarvae there was a rapid decline in zooplankton numbers, particularly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 16 publications
(28 reference statements)
3
37
1
1
Order By: Relevance
“…Therefore, it is not surprising that numerous studies have indicated that a diet including zooplankton increases the growth and survival rates in juvenile crayfish and shrimp (Penaeid sp.) (Coman et al, 2003;Geddes et al, 1991;Mitchell & Collins, 1989;Smallridge et al, 1989;Verhoef et al, 1998). It is commonly believed that following the juvenile stage crayfish no longer posses the dexterity to capture zooplanktonic prey (Sierp & Qin, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, it is not surprising that numerous studies have indicated that a diet including zooplankton increases the growth and survival rates in juvenile crayfish and shrimp (Penaeid sp.) (Coman et al, 2003;Geddes et al, 1991;Mitchell & Collins, 1989;Smallridge et al, 1989;Verhoef et al, 1998). It is commonly believed that following the juvenile stage crayfish no longer posses the dexterity to capture zooplanktonic prey (Sierp & Qin, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…In general, little is known about the zooplankton dynamics in tropical estuaries, and according to Buskey [11], zooplankton rarely have been studied concurrently in tropical or temperate estuaries, even less studies exists on shrimp ponds. Studies of zooplankton in shrimp ponds have shown that these are complex assemblages with rapid temporal changes in structure [4]. The main factors influencing these changes are variations in source of food, predation and the influences of variations in physical and chemical water quality parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The assemblages found in the studied ponds have a variety of roles within the pond ecosystem. Grazing zooplankton influences the dynamics of pond phytoplankton [4]. Predation of zooplankton by shrimp [22] may transfer a significant proportion of the nutrients from natural biota to the shrimp [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because contamination-resistant species in nutrient-rich water can become dominant, the growth of other species can be inhibited, which can decrease diversity. However, many researchers warn against using the zooplankton diversity index as a measure of water quality and have indicated the drawbacks of using the Shannon-Wiener (H) and Simpson (d) indices to calculate zooplankton diversity (Thessen, 2005;Tiwariand Nair, 1998;Senthil, 2002;Coman, 2003).…”
Section: Figure3 Variation Of Cpi During Autumn Winter Summer Andmentioning
confidence: 99%